Surface ultrastructure of the third-instar larvae of Hydrotaea spinigera Stein (Diptera: Muscidae), a fly species of forensic importance - Sukontason K. (2014)
The surface ultrastructure of third-instar larvae of Hydrotaea (=Ophyra) spinigera Stein was observed with scanning electron microscopy. The number of papillae in each anterior spiracle ranges from 5-7. Abdominal segments 4-12 possess ventral welts. Each posterior spiracular disc bears 3 nearly straight slits, with the lower and middle slits closer together than the middle and upper slits. Although the larvae of H. spinigera are generally similar to two other closely-related species in Thailand, Hydrotaea (=Ophyra) leucostoma (Wiedemann) and Hydrotaea (=Ophyra) chalcogaster (Wiedemann), some of the morphological features can help in differentiating these species, thus allowing more accurate identification of species of fly larvae in forensic investigations.